Research data management in clinical neuroscience: the national research data infrastructure initiative - Klingner, Carsten M; Ritter, Petra; Brodoehl, Stefan; Gaser, Christian; Scherag, André; Güllmar, Daniel; Rosenow, Felix; Ziemann, Ulf; Witte, Otto W (Neuroforum, 2021)
Abstract In clinical neuroscience, there are considerable difficulties in translating basic research into clinical applications such as diagnostic tools or therapeutic interventions. This gap, known as the “valley of death,” was mainly attributed to the problem of “small numbers” in clinical neuroscience research, i.e. sample sizes that are too small (Hutson et al., 2017). As a possible solution, it has been repeatedly suggested to systematically manage research data to provide long-term storage, accessibility, and federate data. This goal is supported by a current call of the DFG for a national research data infrastructure (NFDI). This article will review current challenges and possible solutions specific to clinical neuroscience and discuss them in the context of other national and international health data initiatives. A successful NFDI consortium will help to overcome not only the “valley of death” but also promises a path to individualized medicine by enabling big data to produce generalizable results based on artificial intelligence and other methods.